Kajian Dogmatis mengenai Doktrin Corpus Delicti - Remalia Putri Matsino; Farno B.A Gerung; Marde. C.S Mawikere (Peneliti.net, 2021)
This research is a dogmatic study of the doctrine of corpus delicti which is the basis of teaching in the current synod of the Voice of the Gospel Church. The study was carried out using a descriptive qualitative research method which was built from literature research on the book Corpus Delicti by Erastus Sabdono. The results of this study show that the corpus delicti doctrine is built on the basis of a dogmatic study using the inductive method, so that it departs from the problems that occur because of unrest about teaching that is growing at this time, then this doctrine is formulated to provide a new understanding of church teaching so that it turns back. to true teaching. Lack of using the inductive method that underlies a doctrine not based on the Bible itself.